Perbandingan Hasil Belajar IPA Peserta Didik Di SMPN 15 Mataram Yang Menggunakan Model Pembelajaran Discovery Learning Dan Model Pembelajaran Problem-Based Learning - Sahanim, Sahanim; Jamaluddin, Jamaluddin; Bahri, Syamsul; Artayasa, I Putu (Jurnal Ilmiah Pendidikan Indonesia, 2020)
Discovery Learning is a learning model that directs students to activities that can develop process skills in which students are guided to find and to investigate about a concept, so that the knowledge and skills of students are not the result of remembering a set of facts but their own findings. Problem-based learning model is a learning model that emphasizes more on solving problems or problems as a starting point or basis in the learning process. The purpose of this research is to know the differences of sains study result using discovery learning model and problem-based learning model. The type of research used was quasy experiment with pre test desaign and post test group design. The population used in this research is all students of class VII SMPN 15 Mataram. The sample was chosen by Cluster Random Sampling technique and obtained 62 students from Class VIIA and class VIIE students taught by using the discovery learning models, and 62 students from class VIIB and class VIIF students taught by using the problem-based learning models. Instruments test used to measure learning result is tests and non-tests. The test instruments is in multiple choices form, while the non-test instruments uses observation sheets. The result of hypothesis test shows that thitung = 1,76 < ttable = 1,98, which means that there was no difference in result study of sains students by using discovery learning models and problem-based learning models